Skills of learning to learn in medical students from the professor´s perception - Yolanda Cabrera Macias; Annia Esther Vizcaíno Escobar; José Aurelio Díaz Quiñones; Ernesto López Gonzalez; Ernesto López Cabrera; Anaily Puerto Becerra (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2020)
Foundation: the medical university has among its objectives to develop the self-management of knowledge in students, a purpose that can be achieved by training and developing the skills of learning to learn. Objective: to assess the skills formation of learning to learn in medical students at the Medical University of Cienfuegos from the criteria of the professors of the Psychology discipline. Methods: development research based on a descriptive cross-sectional design carried out during the month of February 2018 at the University of Medical Sciences of Cienfuegos, using essentially analytical-synthetic, inductive-deductive, historical-logical and survey methods for collecting information. The universe was made up of the nine professors who teach the discipline of Psychology. Seven variables were explored: how students self-manage knowledge; stimulation of self-management of knowledge; student activities; thinking skills; ways in which students build knowledge; functions of the teacher as mediator of the teaching-learning process; shaping skills of personal development. Results: students self-manage knowledge only in some occasions, preparation for evaluations is insufficient and there is a poor use of the different means for searching information. Conclusions: professors consider that development of the learning to learn skill in the medical students is insufficient.